The therapeutic alliance in cognitive-behavioral therapy for obsessive-compulsive disorder: A systematic review and meta-analysis - Strappini, Francesca; Socci, Valentina; Saliani, Angelo Maria; Grossi, Giuseppe; D’Ari, Giulia; Damato, Titti; Pompili, Nicole; Alessandri, Guido; Mancini, Francesco (Frontiers in Psychiatry, 2022)
Background: The therapeutic alliance has been recognized as one of the most researched key elements of treatment across different therapeutic approaches and diagnostic domains. Despite its importance, our current understanding of its clinical relevance in patients with obsessive-compulsive disorder (OCD) is still debated. This study aimed to examine empirical evidence on the effect of alliance on treatment outcomes in Cognitive Behavioral Therapy (CBT) in patients with OCD in a systematic review and meta-analysis. Methods: Original peer-reviewed articles until March 2022 were included if they were (1) written in English; (2) included a clinical group with a current primary OCD diagnosis; (3) involved individual psychotherapy CBT; (4) used a validated therapeutic alliance scale that was related to the outcome measurement; (5) reported an effect size. Results: Thirteen studies were included, six of which contained sufficient statistical information to be included in the meta-analysis. A total of 897 patients took part in all reviewed studies. We found a modest effect of alliance on post-treatment outcome (Tau2 = -0.1562 [C.I. 95%: -0.2542 to -0.0582]). Discussion: The results show the existence of considerable variability and methodological inconsistencies across studies. We discuss the role of methodological factors that could account for this divergence, the research limitations, and the implications for current research.